A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan - Komai, Tomoyuki; Kohtsuka, Hisanori (Zootaxa, 2017)
A new species of the rare caridean genus Bresilia Calman, 1896, B. cinctus, is described and illustrated on the basis of a single ovigerous female specimen collected from Sagami Bay, central Japan, at 218–318 m depth. The new species is morphologically most similar to B. rufioculus Komai & Yamada, 2011, known only from shallow water cave of Ie Island (depths 14–17 m), Okinawa Islands, Ryukyu Islands, but many characters, including the proportionally shorter rostrum, the well developed suborbital lobe of the carapace, and the presence of a spiniform seta on the ventral surface of the pereopod 1 palm, immediately distinguish the new species from B. rufioculus. Bresilia cinctus n. sp. is the first species of the genus known from the Japanese main islands. The discovery of the new species led us to reassess the merit of the informal division of Bresilia proposed by Komai & Yamada (2010). An identification key to the ten named species of Bresilia is presented.